Risk-Averse Suppliers’ Optimal Pricing Strategies in a Two-Stage Supply Chain - Rui Shen; Zhiqing Meng; Xinsheng Xu; Min Jiang (Discrete Dynamics in Nature and Society)
Risk-averse suppliers’ optimal pricing strategies in two-stage supply chains under competitive environment are discussed. The suppliers in this paper focus more on losses as compared to profits, and they care their long-term relationship with their customers. We introduce for the suppliers a loss function, which covers both current loss and future loss. The optimal wholesale price is solved under situations of risk neutral, risk averse, and a combination of minimizing loss and controlling risk, respectively. Besides, some properties of and relations among these optimal wholesale prices are given as well. A numerical example is given to illustrate the performance of the proposed method.